Different mechanisms of oxygenator failure and high plasma von Willebrand factor antigen influence success and survival of venovenous extracorporeal membrane oxygenation. - Tamara Steiger; Alois Philipp; Karl-Anton Hiller; Thomas Müller; Matthias Lubnow; Karla Lehle (PLoS ONE)
Objective Failure of membrane oxygenator (MO) function of venovenous extracorporeal membrane oxygenators (VV ECMO) remains problematic. The development of device-induced coagulation disorder (COD) or worsened gas transfer (WGT) necessitates a system exchange. The aim was to correlate von Willebrand factor antigen (vWF:Ag) with the predisposition to MO failure and mortality. Methods Laboratory parameters (inflammation, coagulation) and ECMO-related data from 31 VV ECMO patients were analyzed before and after the first MO exchange. Study groups were identified according to the exchange reasons (COD, WGT) and the extent of vWF:Ag (low, ≤425%; high, >425%). Results vWF:Ag remained unchanged after system exchange. High vWF:Ag was associated with systemic endothelial activation of older and obese patients with elevated SOFA score, increased norepinephrine and higher requirement of continuous renal replacement therapy without an effect on MO runtime and mortality. Including the mechanism of MO failure (COD, WGT), various patient group emerged. COD/low vWF:Ag summarized younger and less critically ill patients that benefit mainly from ECMO by a significant improvement of their inflammatory and coagulation status (CRP, D-dimers, fibrinogen) and highest survival rate (91%). Instead, WGT/high vWF:Ag presented older and more obese patients with a two-digit SOFA score, highest norepinephrine, and aggravated gas transfer. They benefited temporarily from system exchange but with worst survival (33%). Conclusions vWF:Ag levels alone cannot predict early MO failure and outcome in VV ECMO patients. Probably, the mechanism of clotting disorder in combination with the vWF:Ag level seems to be essential for clot formation within the MO. In addition, vWF:Ag levels allows the identification different patient populations In particular, WGT/high vWF:Ag represented a critically ill population with higher ECMO-associated mortality.